Urgensi Materi Mahfudzat dalam Menumbuhkembangkan Karakter Anak di Sanggar Genius Ngrupit - Ibnu Hamdan Muzakki; Juliyanto; Pipit Septiana Solikha (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2023)
This study aims to analyze the urgency and implementation of mahfudzat material in the Genius Ngrupit studio that is able to develop potential and character in children. In an era that has developed and developed, Islamic education is the foundation for revitasliing moral values for one's person. The source of knowledge that instills the value of moral education is taught by teaching mahfudzat. Because it is able to give positive strength to those who study it seriously. The teachings contained in mahfudzat are moral values that can increase one's motivation and status. By using a descriptive qualitative approach, so that the data analysis is carried out by multiplying and finding patterns of relationships according to the actual data about mahfudzat material. Important findings in this study are the concept of character education, the learning pattern of mahfudzat material in the Genius Ngrupit studio and the analysis of the urgency and essence of mahfudzat in growing children's character.